Analytical modeling and experimental validation of residual stress in micro-end-milling. Issue 9 (December 2016) - Peng, F.; Dong, Qiong; Yan, Rong; Zhou, Lin; Zhan, Ce
Abstract Micro-milling is widely used in aerospace and precision optical part manufacturing. Residual stress is an important index of surface integrity, which signally affects the performance of the micro-parts. This paper presents an analytical model to predict micro-milling residual stresses considering tool edge radius, material strengthening effects, and initial stress. A micro-milling cutting force prediction model is proposed, in which tool edge radius and material strengthening effects are taken into account. The imaginary heat source is utilized to estimate the temperature distribution in the workpiece. This model considers the prediction results of cutting force and temperature as thermomechanical loads experienced by the workpiece. Also, the effect of initial stress is taken into account during the estimation of residual stresses. After loading, unloading, and stresses release, the results of residual stresses in micro-milling are finally obtained. Both the micro-milling cutting force and residual stresses prediction results are validated by NAK80 steel on a three-axis ultra-precision machine. The predicted results capture the experiment results well in terms of distribution and value. Finally, the model is analyzed and discussed. The influences of tool edge radius, rake angle, feed per tooth, and spindle speed on residual stresses are preliminarily explored.